Trading cooperation of Vietnam with Russia under the current global turbulence - E. S. Novikova; Huu Phu Nguyen; Hoang Anh Le (Вестник университета)
The relevance of the study is determined by the significance, as well as the potential for further development of economic relations between Russia and Vietnam in the context of the current global situation. The purpose of the study is to identify opportunities to intensify trade interaction between the two countries with the additional opportunities analysis to increase exports and imports. Statistical information on the existing trade interaction between Russia and Vietnam has been given, the potential for the tourism activities and educational services development considered. In addition, the article describes the possibilities of increasing the economic potential of the two countries in terms of infrastructure development, including opportunities for the investment joint projects development. Special attention has been paid to the logistics systems development, which can increase the trade cooperation efficiency between Russia and Vietnam, considering the new transportation corridors development within the framework of the Northern Sea Route and Russia’s participation in China’s One Belt, One Road project. The key problems slowing down the possibilities of more active interaction between the two countries have been identified, and possible ways to solve them found. The practical significance consists in the obtained results application in the field of business organization within the two economies, as well as for the analysis and better understanding of economic relations between Russia and Vietnam.